Influence of Body Mass Index on Functional Capacity in Physically Active Community-Dwelling Adult Women - De Moraes-Ferrari, G (WILEY, 2026)
Background: Declining functional capacity is a major contributor to disability in older populations. This study aimed to examine the association between body mass index (BMI) and physical function in physically active adult women. Methods: A cross-sectional analysis was conducted on 515 women aged 46-90 years participating in a free community-based physical activity program in Brazil. Functional capacity was assessed using handgrip strength, trunk flexibility, lower limb muscle strength (LLMS), and walking speed. Participants were classified by BMI into underweight (< 22 kg/m(2)), eutrophic (22-27 kg/m(2)), overweight (27-30 kg/m(2)), and obese (>= 30 kg/m2). One-way ANOVA with Bonferroni post hoc tests and hierarchical multiple regression analyses were used to assess differences and associations. Results: Overweight and obese participants represented the largest proportions (27.2% and 25.6%, respectively). Walking speed was slower in obese participants (1.0 m/s) than in the eutrophic group (1.1 m/s), but this difference was not statistically significant (p > 0.05). Trunk flexibility was significantly lower in the obese group (21.3 cm vs. 26.3 cm, p < 0.05). LLMS was significantly associated with walking performance across all BMI categories. Conclusion: Higher BMI is associated with reduced flexibility and mobility in adult women. LLMS appears critical for maintaining functional independence.